Sistem Entri Resep Dokter Terkomputerisasi dalam Sistem Informasi Rumah Sakit: Literature Review - Rudi Ilhamsyah; Winny Setyonugroho (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Background: “To err is human” stated by Institute of Medicine showing the abundance of medication prescription errors which compromises patient safety and exaggerates health care cost. These errors could be prevented by the introduction of health information technology such as Electronic Medical Records. Method: The researcher conducted the literatures study to confirm the choice of the keywords, then do a search in 4 databases (PubMed, ScienceDirect, EBSCO, dan ProQuest) from that databases, we screened it based on its title, then its abstract and then the full paper. At the end, we checked if it’s Scopus-Indexed, we included it in the analysis. Result: 40 journals that were stated to be included in this analysis, grouped by study site, whether one-center or multi-center. 26 journals are one-center. From 40 journals, only 2 types of CPOE that are shared by different hospitals and only 3 types of CDSS that are shared by different hospitals. Both CPOE and CDSS are mostly a commercial program. Conclusion: There is no sufficient explanation of the existence of the most trustful institution which controls the production and the development of CPOE and CDSS.